2010
DOI: 10.1007/s10482-010-9528-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety and regulation of yeasts used for biocontrol or biopreservation in the food or feed chain

Abstract: Yeasts have been important components of spontaneous fermentations in food and beverage processing for millennia. More recently, the potential of utilising antagonistic yeasts, e.g. Pichia anomala and Candida spp., for post-harvest biological control of spoilage fungi during storage of plant-derived produce ('biopreservation') has been clearly demonstrated. Although some yeast species are among the safest microorganisms known, several have been reported in opportunistic infections in humans, including P. anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 22 publications
0
49
0
1
Order By: Relevance
“…Most yeast are harmless to humans; however, even established food yeasts like S. cerevisiae have on occasion been reported to be involved in clinical outbreaks (Murphy and Kavanagh 1999). Identifying the factors involved in the virulence of H. anomala and the differentiation of pathogenic and non-pathogenic strains will be of central importance for the future biotechnical applications of this yeast (Sundh and Melin 2010).…”
Section: Strain Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most yeast are harmless to humans; however, even established food yeasts like S. cerevisiae have on occasion been reported to be involved in clinical outbreaks (Murphy and Kavanagh 1999). Identifying the factors involved in the virulence of H. anomala and the differentiation of pathogenic and non-pathogenic strains will be of central importance for the future biotechnical applications of this yeast (Sundh and Melin 2010).…”
Section: Strain Diversitymentioning
confidence: 99%
“…This yeast has been isolated from many different habitats and shows a remarkable physiological robustness towards environmental stresses, such as extreme pH or low water activity (Walker 2010 its anti-microbial activity, it is traditionally viewed as a biopreservation agent (Jijakli 2010;Schnürer and Jonsson 2010), but novel applications, such as enzyme production or feed improvement, are also under study. Issues of regulation and formulation, commonly overlooked by university microbiologists, were discussed during this symposium Sundh and Melin 2010). The taxonomy debate revealed that there is a growing interest in H. anomala and its relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Charkrabarti et al 2001), with regard to food safety aspects P. anomala is classed at biosafety level 1 (De Hoog, 1996) and is considered safe for healthy individuals. In fact, P. anomala currently has QPS (qualified presumption of safety) status from EFSA (European Food Safety Authority) and this has benefits in terms of public perspectives of food biotechnology and acceptability of novel microorganisms in food (Sundh and Melin 2010). Ray and Nanda (1996); Satyanarayana (2010) Brewing Anti-gushing potential in malting barley Olstorpe et al (2009a); Laitila et al (2007; P. anomala in the environment With regard to the natural niche of P. anomala, this yeast has been isolated from very diverse sources.…”
Section: Introductionmentioning
confidence: 99%
“…Sundh and Melin (2010) discuss the situation, with focus on the use of P. anomala and other yeasts in feed and food applications. The Qualified Presumption of Safety (QPS) approach for safety assessments of microorganisms intentionally added to food or feeds has been developed by the European Food Safety Authority (EFSA).…”
Section: Barriers To Practical Applicationsmentioning
confidence: 99%
“…The intention is to provide efficient assessments of microbial species where a sufficient body of knowledge or long-term experience testifies to their safety. P. anomala is one of several yeast species that have been given QPS status, although QPS was later restricted to the use of this yeast for production purposes (Sundh and Melin 2010).…”
Section: Barriers To Practical Applicationsmentioning
confidence: 99%